An Exploration of Child–Staff Interactions That Promote Physical Activity in Pre-School - Kippe, Karin Oddbjørg; Fossdal, Tom Stian; Lagestad, Pål Arild (Frontiers in Public Health, 2021)
A previous study by Authors (a) identified a significant association between the preschool staff’s and children’s average physical activity levels during preschool hours, but did not determine if this association was initiated by preschool staff or children. The aim of the present study was to explore the interactions between children and staff to better understand the conditions of such a relationship. Observations were carried out in three preschools, and a focus-group interview and semiformal interviews were conducted with five preschool staff in one of the three preschools to examine the research question. Both the observations and interview data revealed that preschool staff’s physical-activity initiated physical activity among the children. The findings point to the importance of preschool staff as organizers of children’s physical activity, and that the staff’s willingness to join a physical activity initiated by the children also appears to be important. The findings also indicate that most of the physical activity took place outdoors. The study highlights the importance of preschool staff as major contributors to preschool children’s physical activity.